Balanced Unemployment in Polish Economy - Kamila Szymańska (Contemporary Economics)
The article deals with the problem of balanced unemployment in relation to the Polish economy. This issue with its variety considerations and economic, social and political implications is today one of the most important matter. Author analyses this problem together with its reasons and refer it to the Polish economy. In first and second part of the text there are presented basic assumptions of natural unemployment theory and Non-Accelerating Inflation Rate of Unemployment. Third part is an analysis of balanced unemployment in the Polish economy